Typology of Language Taboos in the Domains of the Body and Sexuality in Acehnese Society - Junaidi Junaidi; Eli Nurliza; Nurul Azmi; Harunnun Rasyid; Musrian Sari Lase; Vera Wardani (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Language functions not only as a means of communication but also as a reflection of social values, norms, and cultural systems. In Acehnese society, language use is governed by politeness norms that prohibit the utterance of expressions considered taboo, vulgar, or offensive. Previous studies have generally discussed language taboo in broad social contexts, yet no study has specifically examined the typology of taboo language in the domains of the body and sexuality from a sociopragmatic perspective. This study aims to identify the typology of language taboo in those domains and explain its social functions and management strategies in Acehnese interaction. The study employed a descriptive qualitative method within a sociopragmatic framework. Data were collected from 30 native Acehnese speakers through participant observation, semi-structured interviews, recording, note-taking, and documentation techniques. Data analysis involved data reduction, data presentation, and conclusion drawing, while source triangulation ensured validity. The findings reveal four categories of taboo language: expressions related to sexual activities, genitalia and sexual organs, disgusting body parts or biological substances, and certain body parts considered inappropriate in specific contexts. Acehnese speakers generally avoid direct expressions and instead use euphemisms, metaphors, or lexical substitutions to maintain politeness and social harmony. The study confirms that taboo language functions as a social mechanism for preserving harmony, preventing conflict, and maintaining cultural values in Acehnese society. These findings contribute to sociopragmatic studies by demonstrating that taboo expressions are connected to cultural beliefs, religious values, and norms governing interpersonal communication in Acehnese communities.